Metal-as-insulation sub-scale prototype tests under a high background magnetic field. (30th July 2018) - Fazilleau, Philippe; Borgnic, Benjamin; Chaud, Xavier; Debray, François; Lécrevisse, Thibault; Song, Jung-Bin
Abstract: The aim of the NOUGAT project is to design and realize a 10 T high temperature superconducting solenoidal insert able to operate in a 20 T background magnetic induction. Our design is based on the metal-as-insulation winding technique consisting of co-winding a bare REBCO high temperature superconducting tape with a stainless steel tape. The metal-as-insulation winding maintains the self-protection feature of the no insulation winding and helps to reduce current charging time constants—one of the major drawbacks of no insulation coils—by significantly increasing the turn-to-turn electrical resistance. First, we demonstrated the self-quench protective behavior at 4.2 K under a high field up to 17 T by testing a single-pancake prototype. Then, before fabricating the final insert, we designed, wound and tested a second prototype made of two double-pancakes. The purposes were three-fold: validating the winding and assembly process, confirming the operating margins and corroborating the mechanical study. In this article, we present the main results of the tests performed at 4.2 K on this sub-scale prototype in a high background magnetic field at Laboratoire National des Champs Magnétiques Intenses at Grenoble.